2015
DOI: 10.1039/c4ta06871h
|View full text |Cite
|
Sign up to set email alerts
|

A black–red phosphorus heterostructure for efficient visible-light-driven photocatalysis

Abstract: A new single elemental heterostructure of black–red phosphorus was prepared, which exhibited high visible-light-driven photocatalytic activity comparable to that of CdS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
162
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 238 publications
(170 citation statements)
references
References 24 publications
6
162
0
2
Order By: Relevance
“…The in-plane Young's modulus of single-layer BP was 41.3 GPa in the direction perpendicular to the pucker and 106.4 GPa in the parallel direction, and the ideal strains were 0.48 and 0.11 in the perpendicular and parallel directions, respectively [68]. Second, advancements have been made to enhance the stability of few-layer BP in ambient air [56,63,64]. All the properties mentioned above render BP very attractive for achieving low-friction and low-wear regimes.…”
Section: Potential Of Bp As Lubricantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The in-plane Young's modulus of single-layer BP was 41.3 GPa in the direction perpendicular to the pucker and 106.4 GPa in the parallel direction, and the ideal strains were 0.48 and 0.11 in the perpendicular and parallel directions, respectively [68]. Second, advancements have been made to enhance the stability of few-layer BP in ambient air [56,63,64]. All the properties mentioned above render BP very attractive for achieving low-friction and low-wear regimes.…”
Section: Potential Of Bp As Lubricantsmentioning
confidence: 99%
“…Owing to the aforementioned attractive properties of BP, the exploration of relevant applications has made rapid progress in the fields of electronics, field-effect transistors [58,59], sensors [60], energy storage [60−62], batteries [63], photocatalysis [64,65], and optoelectronics [66], and other applications.…”
Section: Bp Applicationsmentioning
confidence: 99%
“…On the other hand, its possibility as a water splitting photocatalyst has not been studied much. Recently, several researches adopted black phosphorus as a photocatalyst or photoelectrode [8,9,10]. Zhou et al [8] proposed TiO 2 , black phosphorus heterostructure for the solar cell and Sa et al [9] suggested strain engineering of the black phosphorus for its future application as a photocatalyst.…”
Section: Black Phosphorus As Water Splitting Photocatalystmentioning
confidence: 99%
“…Due to its distinct properties compared with other two-dimensional materials, black phosphorus is extensively studied in field effect transistors and other electronic devices [4,5,6,7]. In recent years, according to several researches, it is reported that black phosphorus can also be a promising candidate for solar water splitting [8,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…Although such phosphorene-based hetero-structures are widely reported in experiment and theory, type-II band alignment heterostructures are extremely scarce, only being BP/MoS 2 , 18,27,28 BP/GaAs 29 as well as black−red phosphorus heterostructures. 30 Therefore, desirable type-II phosphorene-based heterostructures preferably with a large built-in potential for driving electrons and holes deserve to be explored in experiment and theory.…”
mentioning
confidence: 99%